Utilizing the innovation potential of suppliers in construction projects. Issue 2 (22nd January 2018) - Sariola, Rami
Abstract : Purpose: The manufacturers of construction components and materials are the suppliers in construction projects, and represent a significant portion of their value. However, their knowledge is not used sufficiently when it comes to construction innovation. This research paper focuses on the suppliers' innovation potential in construction projects. The purpose of this paper is to identify practices for enhancing the contractor–supplier relationship and using the suppliers' innovation potential in construction projects. Design/methodology/approach: A qualitative exploratory research strategy is used in the context of construction projects. In total, 18 interviews were conducted with contractors to discover the experiences and practices related to the contractor–supplier relationship and construction innovation. Findings: The contractors perceive that the suppliers have innovation potential, and that they are often a source of construction innovation. The findings reveal business- and project-level practices for enhancing the contractor–supplier relationship and for overcoming barriers that hinder the suppliers' innovation potential. Research limitations/implications: The research conducted for this paper is limited to the contractors' perspectives based on construction projects in one country. Further research is encouraged to verify the success of identified practices and cover the perspectives of the suppliers, clients and designers. Originality/value: Limited research and attention is directed toward the role of the suppliers in projects within the construction industry. This paper offers important information about the part that both the suppliers and the contractors play in construction innovation and its facilitation.